2021
DOI: 10.1111/1911-3838.12254
|View full text |Cite
|
Sign up to set email alerts
|

Resilience, Psychological Distress, and Academic Burnout among Accounting Students*

Abstract: This study's objective is to examine the role of resilience in the dynamic between academic burnout and psychological distress using a sample of US undergraduate accounting majors. It extends prior research—that is, García‐Izquierdo et al. (2018), who examine these relationships using a sample of Spanish nursing students. For this study, a survey instrument was concurrently administered to 443 accounting majors at four geographically dispersed universities. Two alternative models are tested. The first model po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 77 publications
0
4
0
1
Order By: Relevance
“…6 This study utilized identical resilience and psychological distress measures as those used in this study. In contrast, Smith and Emerson ( 2021 ), using identical measures, found among a sample of accounting students that resilience only moderated one of the paths between the elements of burnout and psychological distress and that the predictive ability of the model was enhanced with resilience serving as an exogenous predictor rather than a moderator.…”
Section: Potential Moderating Effectsmentioning
confidence: 90%
See 1 more Smart Citation
“…6 This study utilized identical resilience and psychological distress measures as those used in this study. In contrast, Smith and Emerson ( 2021 ), using identical measures, found among a sample of accounting students that resilience only moderated one of the paths between the elements of burnout and psychological distress and that the predictive ability of the model was enhanced with resilience serving as an exogenous predictor rather than a moderator.…”
Section: Potential Moderating Effectsmentioning
confidence: 90%
“… 5 Smith and Emerson ( 2021 , pp. 247–248) acknowledge that the relationship between psychological distress and academic burnout may be non-recursive, a phenomenon only testable via a study of longitudinal design.…”
mentioning
confidence: 99%
“…Prior studies have investigated the association between psychological distress and academic burnout but reached the opposite conclusion. Smith and Emerson (2021) have indicated that academic burnout and its dimensions had effects on psychological distress, whereas other scholars thought that negative emotions worsened academic burnout (Salmela-Aro et al, 2009;Zhang et al, 2022). Existing research, however, has primarily focused on college students, and this relationship among junior high school students was not well explored.…”
Section: The Role Of Psychological Distressmentioning
confidence: 99%
“…Studies have shown that female students are more affected by academic burnout than male students due to their different psychological states (5). Smith and Emerson (6) reported that psychological distress had significant positive associations with academic burnout in undergraduate students.…”
Section: Introductionmentioning
confidence: 99%